INTEGRASI PERKEBUNAN SAWIT DAN PETERNAKAN SAPI DI DESA TEUPIN PANAH KECAMATAN KAWAY XVI, ACEH BARAT - Syahril Syahril; Helmi Noviar; Affandi Affandi; Damrus Damrus; Saiful Badli (Jurnal Pengabdian Agro and Marine Industry, 2021)
Sustainable economic development is urgently needed by developing countries, one form of which is the stability of the price of fresh oil palm fruit bunches and being able to integrate with cattle farming by utilizing the area around oil palm land by creating effectiveness and efficiency for farmer groups, so as to increase their income in the future. will come. activities carried out in the form of socialization and transfer of knowledge to the community. The time for the implementation of the activity lasts for 1 (one) day on October 20, 2019. The subject of this service is the Community of Farmers and Livestock in Teupin Panah Village, Assisted Village, Faculty of Economics, Teuku Umar University. The participants were very enthusiastic about participating in this activity and actively asked and responded to the material presented by the speakers. In general, this activity consists of two sessions. The first session was a material presentation session, while the second session was an interactive discussion. The stability of the price of oil as a key variable in determining the welfare of oil palm farmers is a prerequisite that must be met. The volatile palm oil price fluctuation will be very risky to the welfare level of farmers. In addition, other solutions are needed in an effort to ensure that farmers' income is not reduced from price uncertainty factors. One of the efforts that can be done is by integrating oil palm plantations with cattle farming. This idea was proposed based on the potential of the oil palm plantation area in Teupin Panah village which is relatively large to be used for oil palm cultivation, especially for smallholder plantations..